ATTITUDES OF MICRO WOMAN ENTREPRENEURS TOWARD COOPERATIVES IN OSMANELI DISTRICT OF BILECİK PROVINCE - PEKTAŞ, Selin (SSD Journal, 2020)
In recent years, following the entry of Turkish women in working life, Turkish women began to take more active role in the business life. Women who started working to contribute to their home economy, increased their economic well-being and started to have a voice in the economic sense. Especially with the development of social media, housewives created a new market for themselves to sell many of their handcrafted products. At the same time, the conscious society and social responsibility projects created for women have also been effective in women’s economic voice. In the light of these developments, employment opportunities for the women who work were increased and formed the ground for strengthening women’s entrepreneurship. The research was conducted on women who exhibited their efforts within the scope of an education center called “Sürekli Eğitim Merkezi”, which started operating in 2016 within the Municipality of Osmaneli, Bilecik province, and the Osmaneli Women Entrepreneurs Cooperative, which started operating in 2019. The sample size of the study consists of 40 women entrepreneurs in the Sürekli Eğitim Merkezi and Osmaneli Women Entrepreneurs Cooperative. In line with the information obtained, the level of susceptibility to cooperatives and their impact on women’s economic lives were examined and aimed to set an example for other micro women entrepreneurs.